Scientific criticism and refereeing of scientific papers. An unavoidable point of view - Juan Ramón García Díaz (Journal of the Selva Andina Animal Science)
Scientific criticism is fundamentally based on the evaluations and analyzes that are carried out during the arbitration or review of scientific works, being essential to achieve the truth, the supreme objective of science, an activity of a controversial nature. Scientific criticism, which is not always accepted by researchers, must be based on the scientific method, from an ethical perspective. If this is achieved, it becomes a key instrument in the collective conformation of scientific knowledge. The criticism of a scientific work is the fundamental criterion to discard or accept the results of the investigation, if it is right and it is accepted, the solution of the experiment is discarded and it is reconsidered, and if it is rejected, its results are accepted. The criticism of a scientific work has its greatest responsibility with the scientific truth, therefore it must be fair, objective, ethical, contribute to the improvement of an investigation, unite opinions and manage to open the dialogue and debate of its results. In addition, scientific criticism must be educational for the autor (s) of scientific work and form values, by fully developing their own capacities, with a sense of social and scientific responsibility. Being receptive to scientific criticism is a goal to be achieved by researchers, and indicates their scientific maturity, in their exercise, personal interests should not prevail over the interests of science. Publications are important for researchers, especially at the beginning of their academic life since they are judged or recognized for them and because, in addition, to publish they must face and defend their work against scientific criticism, which contributes to their maturity to scientific work. The publication of the work essentially depends on the ability of the authors to convince the reviewers of their worth. For the publication of a scientific article, arbitration is required, one of the forms of scientific criticism. The review process varies according to the journal, however, the most common systems are blind and double-blind, which unquestionably guarantee the quality of the publications. The arbitration or review of a scientific work is a critical exercise carried out by the arbitrator (a) or reviewer (a) in order to clarify the doubts that a detailed and conscientious reading would have left. It constitutes the mature and ethical form of scientific criticism, a work of scientific creation, an assessment that allows the search for truth as the main objective of science. The arbitration of a scientific work is an act of learning, and a possibility of self-taught professional improvement, which is based on fair analysis, impartiality, objectivity and altruism. It begins with the choice of the arbitrator (a) or reviewer (a) and lasts forever because a published result belongs to society and will be subject to refutation or improvement through criticism from the scientific community. The arbitrator (a) or reviewer (a) must be a professional of high professional prestige and authority in academic circles, have theoretical and practical experience and investigative history that endorse it, be objective in their assessments, ethical and avoid bias. haughtiness Criticize the scientific basis of the work, but do not personally attack the author.